2021
DOI: 10.1139/cjm-2019-0461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated warming on bacterial diversity and abundance in tropical soils from East Malaysia using open top chambers

Abstract: The effects of global warming are increasingly evident, where global surface temperatures and atmospheric concentration of carbon dioxide have increased in past decades. Given the role of terrestrial bacteria in various ecological functions, it is important to understand how terrestrial bacteria would respond towards higher environmental temperatures. This study aims to determine soil bacterial diversity in the tropics and their response towards in situ warming using an open-top chamber (OTC). OTCs were set up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The warming impact and heat entrapment of soils inside the OTCs are validated in various studies. The difference in soil temperature between the treatment plots and control plots was between 0.81 °C to 1.15 °C (Chua and Wong, 2021), similar result is reported by Bokhorst et al (2011) (0.5 °C to 1.4 °C). A study by Yergeau et al (2011) recorded an average soil surface temperature of 0.7 °C inside OTC, while Camac et al (2015) observed a 1.2 °C increase in average soil surface temperature.…”
Section: Use Of Open-top Chamber (Otc) As Simulated Warming Modelsupporting
confidence: 85%
See 4 more Smart Citations
“…The warming impact and heat entrapment of soils inside the OTCs are validated in various studies. The difference in soil temperature between the treatment plots and control plots was between 0.81 °C to 1.15 °C (Chua and Wong, 2021), similar result is reported by Bokhorst et al (2011) (0.5 °C to 1.4 °C). A study by Yergeau et al (2011) recorded an average soil surface temperature of 0.7 °C inside OTC, while Camac et al (2015) observed a 1.2 °C increase in average soil surface temperature.…”
Section: Use Of Open-top Chamber (Otc) As Simulated Warming Modelsupporting
confidence: 85%
“…Planctomycetes and Actinobacteria are better acclimated to higher temperatures, while other bacterial groups, like Acidobacteria, Betaproteobacteria and Deltaproteobacteria experience a decrease in relative abundance as the temperature rises (Rui et al, 2015). Research done by Chua and Wong (2021) showed that increases in the relative abundance of Actinobacteria and Chloroflexi were observed after twelve months of in situ OTC-simulated warming, while a significant decrease in the relative abundance of Bacteroidetes was recorded.…”
Section: Global Warming and Its Effects On Bacterial Diversity And Pl...mentioning
confidence: 99%
See 3 more Smart Citations